Sporophyte Formation and Life Cycle Completion in Moss Requires Heterotrimeric G-Proteins . Issue 2 (22nd August 2016) - Hackenberg, Dieter; Perroud, Pierre-François; Quatrano, Ralph; Pandey, Sona
Abstract : Physcomitrella patens heterotrimeric G-proteins affect gametophore elongation and are essential for sporophyte formation, suggesting their unique role in life cycle completion in early land plants. Abstract: In this study, we report the functional characterization of heterotrimeric G-proteins from a nonvascular plant, the moss Physcomitrella patens. In plants, G-proteins have been characterized from only a few angiosperms to date, where their involvement has been shown during regulation of multiple signaling and developmental pathways affecting overall plant fitness. In addition to its unparalleled evolutionary position in the plant lineages, the P. patens genome also codes for a unique assortment of G-protein components, which includes two copies of Gβ and Gγ genes, but no canonical Gα . Instead, a single gene encoding an extra-large Gα (XLG) protein exists in the P. patens genome. Here, we demonstrate that in P. patens the canonical Gα is biochemically and functionally replaced by an XLG protein, which works in the same genetic pathway as one of the Gβ proteins to control its development. Furthermore, the specific G-protein subunits in P. patens are essential for its life cycle completion. Deletion of the genomic locus of PpXLG or PpGβ2 results in smaller, slower growing gametophores. Normal reproductive structures develop on these gametophores, but they are unable to form any sporophyte, the only diploid stage in the moss life cycle. Finally, the mutant phenotypes of ƊPpXLG and ƊPpGβ2 can be complemented by the homologous genes from Arabidopsis, AtXLG2 and AtAGB1, respectively, suggesting an overall conservation of their function throughout the plant evolution.